Revealing the Venomous Secrets of the Spider's Web - Esteves, Franciele Grego [UNESP]; Dos Santos-Pinto, José Roberto Aparecido [UNESP]; Ferro, Milene [UNESP]; Sialana, Fernando J.; Smidak, Roman; Rares, Lucaciu Calin; Nussbaumer, Thomas; Rattei, Thomas; Bilban, Martin; Bacci Júnior, Mauricio [UNESP]; Lubec, Gert; Palma, Mario Sergio [UNESP] (American Chemical Society (ACS), 2020)
Orb-weaving spiders use a highly strong, sticky and elastic web to catch their prey. These web properties alone would be enough for the entrapment of prey; however, these spiders may be hiding venomous secrets in the web, which current research is revealing. Here, we provide strong proteotranscriptomic evidence for the presence of toxin/neurotoxin-like proteins, defensins, and proteolytic enzymes on the web silk from Nephila clavipes spider. The results from quantitative-based transcriptomic and proteomic approaches showed that silk-producing glands produce an extensive repertoire of toxin/neurotoxin-like proteins, similar to those already reported in spider venoms. Meanwhile, the insect toxicity results demonstrated that these toxic components can be lethal and/or paralytic chemical weapons used for prey capture on the web, and the presence of fatty acids in the web may be a responsible mechanism opening the way to the web toxins for accessing the interior of prey's body, as shown here. Comparative phylogenomic-level evolutionary analyses revealed orthologous genes among two spider groups, Araneomorphae and Mygalomorphae, and the findings showed protein sequences similar to toxins found in the taxa Scorpiones and Hymenoptera in addition to Araneae. Overall, these data represent a valuable resource to further investigate other spider web toxin systems and also suggest that N. clavipes web is not a passive mechanical trap for prey capture, but it exerts an active role in prey paralysis/killing using a series of neurotoxins.
Keywords: de novo transcriptome assembly; LCMS-based proteomics; neurotoxins; spider silk-producing glands; web silk toxins